2020
DOI: 10.2147/ott.s254634
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA TUG1 Promotes Cell Proliferation and Inhibits Cell Apoptosis, Autophagy in Clear Cell Renal Cell Carcinoma via MiR-31-5p/FLOT1 Axis</p>

Abstract: Purpose: Clear cell renal cell carcinoma (ccRCC) is a common urological carcinoma in adults. Long non-coding RNA (lncRNA) taurine-upregulated gene 1 (TUG1) has been reported to be involved in the progression of diverse human cancers, including renal cell carcinoma (RCC). However, the biological mechanism of TUG1 was rarely reported in ccRCC. Methods: The levels of TUG1, microRNA miR-31-5p and flotillin 1 (FLOT1) in ccRCC tissues and cells were detected by qRT-PCR. The interactions between miR-31-5p and TUG1 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Cell apoptosis was detected using the Annexin V-FITC cell apoptosis kit (Beyotime, China) according to a previously described method [ 36 ]. After transfection, the cells were collected and washed with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Cell apoptosis was detected using the Annexin V-FITC cell apoptosis kit (Beyotime, China) according to a previously described method [ 36 ]. After transfection, the cells were collected and washed with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, LncRNAs inhibit miRNA activity. For example, Lv D et al revealed that Taurine- Upregulated gene 1 (TUG1) is a 7.1-KB lncRNA located on chromosome 22q12, as ceRNA to isolate Mir-31-5p and promote flotillin 1 (FLOT1) to participate in cell membrane structure and mediate intercellular signal transduction 75 . FLOT1 is a lipid raft marker protein, and its n-terminal residues at position 1 to 185 constitute an SPFH (Stomatin, Prohibitin, Flotillin, Hflk/C) domain, which is palmitoylated at C34 site and associated with its localization in lipid raft 76 .…”
Section: Lncrnas and Lipid Metabolismmentioning
confidence: 99%
“…For example, lncRNA TUG1 facilitated the proliferation of ccRCC cells by targeting miR-31-5p and regulating FLOT1 expression. 8 LncRNA DARS-AS1 promoted the tumorigenesis of ccRCC through the miR-194-5p / DARS axis. 9 Recently, a cancer-related lncRNA HCG18 was identified to participate in several malignant cancers, such as bladder cancer, gastric cancer, and nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 97%